Protection of probiotic microorganisms by microencapsulation - Tanja Petrović, Viktor Nedović, Suzana Dimitrijević-Branković, Branko Bugarski, Christophe Lacroix (Chemical Industry and Chemical Engineering Quarterly, 2007)
n/a